2015
DOI: 10.3109/14767058.2015.1031740
|View full text |Cite
|
Sign up to set email alerts
|

Death or survival with major morbidity in VLBW infants born at Brazilian neonatal research network centers

Abstract: More than half of the VLBW infants born at public university level 3 Brazilian hospitals either die or survive with major morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 23 publications
5
38
1
4
Order By: Relevance
“…25 Thus, VLBW infant mortality has been reported to range between 12.4% and 28% as per the neonatal networks of developed countries (the Euro Neo Net/Euro-Peristat Network, 26 the Vermont-Oxford Network, 27 the Canadian Neonatal Network, 28 the National Institute of Child Health and Human Development [NICHD], 29 the Spanish Neonatology Society). 23 In contrast, the results obtained by the Brazilian Neonatal Research Network 30 and the Neonatology Network of Public Hospitals from the City of Buenos Aires 31 describe more unfavorable results, especially associated with a low use of antenatal corticosteroids. However, when analyzing such differences, it is necessary to consider the denominator used to estimate the mortality rate and the fact that inclusion criteria vary from one study to another, 32 in addition to differences in population, perinatal practices, and resources.…”
Section: Discussioncontrasting
confidence: 42%
“…25 Thus, VLBW infant mortality has been reported to range between 12.4% and 28% as per the neonatal networks of developed countries (the Euro Neo Net/Euro-Peristat Network, 26 the Vermont-Oxford Network, 27 the Canadian Neonatal Network, 28 the National Institute of Child Health and Human Development [NICHD], 29 the Spanish Neonatology Society). 23 In contrast, the results obtained by the Brazilian Neonatal Research Network 30 and the Neonatology Network of Public Hospitals from the City of Buenos Aires 31 describe more unfavorable results, especially associated with a low use of antenatal corticosteroids. However, when analyzing such differences, it is necessary to consider the denominator used to estimate the mortality rate and the fact that inclusion criteria vary from one study to another, 32 in addition to differences in population, perinatal practices, and resources.…”
Section: Discussioncontrasting
confidence: 42%
“…The remaining 3 studies didn’t provide these details. [22, 23, 25] The large studies by Carlo et al and Mori et al provided data for all the outcomes included in the review at all the gestation[24, 28]. Guthrie et al provided the data only for the outcome of NEC.…”
Section: Resultsmentioning
confidence: 99%
“…Guthrie et al provided the data only for the outcome of NEC. [29] We obtained additional data on request from authors Mori et al, Bajwa et al and Guinsburg et al[23, 25, 28] We used the systematic review by Park et al for the data on Bader et al and Guthrie et al as we were unable to get it from the original authors. [12, 22, 29] Only 2 studies reported on long-term neurodevelopment at the corrected age of 12–24 months.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary outcome was the presence of a fifth-minute Apgar score of 7–10. Given the chance of the primary outcome in the study centres to be approximately 50%,16 with a 10% difference between the studied groups and a power of 80%, it was necessary to include at least 387 infants in each group.…”
Section: Methodsmentioning
confidence: 99%